Odpowiedzi

2009-04-28T16:32:02+02:00
2(x-2) = x-2
2x - 4 = x - 2
2x - x = -2 + 4
x = 2 -----> odpowiedź 2


-5x + 12 = 0
-5x = -12
x = 12:5 = 2,4 ------> odpowiedź 2,4 [powinnaś to w treści zaznaczyć wyraźniej]


5(x+1) = 3x+11
5x + 5 = 3x + 11
5x - 3x = 11 - 5
2x = 6
x = 3 -------> odpowiedź 3
1 1 1
2009-04-28T16:32:16+02:00
A)

2x-4=x-2
x=2

b)

-5x=-15/:(-5)
x=3

c)

5x+5=3x+11
2x=6/:2
x=3
1 1 1
2009-04-28T16:35:26+02:00
2(x-2)=x-2
2x-4=x-2
2x-x=-2+4
x=2

-5x+12=0
-5x=-12/:(-5)
x=2,4

5(x+1)=3x+11
5x+5=3x+11
5x-3x=11-5
2x=6/:2
x=3
1 5 1